2012
DOI: 10.1007/s11060-012-0958-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anti-glioma activity and in vivo efficacy of the cannabinoid ligand KM-233

Abstract: Glioblastoma multiforme (GBM) is the most common and devastating form of primary central nervous system malignancy. The prognosis for patients diagnosed with GBM is poor, having a median survival rate of 12-15 months. Despite modern advances in the development of antineoplastic agents, the efficacy of newer anti-cancer agents in the treatment of GBM is yet to be determined. Thus, there remains a significant unmet need for new therapeutic strategies against GBM. A promising chemotherapeutic intervention has eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Cannabinoids are in general associated with a reduced invasiveness for various tumor types. 17,19,20,25,37 In contrast, one study reported an increased invasiveness after treatment with cannabinoids in a cannabinoid receptor independent way. 38 The experiments conducted for the present study revealed differentiated effects of cannabinoids.…”
Section: Cannabinoids Change the Cell Motility And Affect The Cell Armentioning
confidence: 98%
See 1 more Smart Citation
“…Cannabinoids are in general associated with a reduced invasiveness for various tumor types. 17,19,20,25,37 In contrast, one study reported an increased invasiveness after treatment with cannabinoids in a cannabinoid receptor independent way. 38 The experiments conducted for the present study revealed differentiated effects of cannabinoids.…”
Section: Cannabinoids Change the Cell Motility And Affect The Cell Armentioning
confidence: 98%
“…16 This indicates that the eCB system is part of the (anti)tumor signaling. Most of the studies analyzing the effects of cannabinoids on tumor cells have focused on apoptosis [17][18][19] or cell cycle arrest. 18,20 Changes and disruptions of the cytoskeleton in a quantitative manner and thus mechanical parameters have been investigated only sparsely.…”
Section: Introductionmentioning
confidence: 99%
“…The submaximal doses of Δ 9 -THC and CBD in combination with TMZ produced a strong antitumoral action in both TMZ-sensitive and TMZ-resistant tumors [108]. Treatment of KM-233 (novel cannabinoid ligand) caused a time dependent change in the phosphorylation profiles of MEK, ERK1/2, Akt, BAD, STAT3, and p70S6K in U87MG human GBM cells [109]. At 12mg/kg daily dose of KM-233 for 20 days revealed around 80% reduction in tumor size in the orthotopic model of U87MG [109].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of KM-233 (novel cannabinoid ligand) caused a time dependent change in the phosphorylation profiles of MEK, ERK1/2, Akt, BAD, STAT3, and p70S6K in U87MG human GBM cells [109]. At 12mg/kg daily dose of KM-233 for 20 days revealed around 80% reduction in tumor size in the orthotopic model of U87MG [109]. Glioma cells develop resistance to cannabinoid treatment due to the upregulation of Amphiregulin (EGFR family ligand) and the growth factor midkine (Mdk) [110-111].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Both receptors, either individually or in combination, have been identified as potential targets for intervention of human diseases including neurodegenerative [4][5][6] and cardiovascular disease, 7-9 diabetes, [10][11][12] and cancer. [13][14][15][16] Within this spectrum of diseases, intervention in neurodegenerative disorders using CB2 agonists and inverse agonists is arguably one of the most exciting developments in the cannabinoid field. Specifically, microglia, the resident immune and inflammatory mediators in the central nervous system (CNS), express CB2 in Alzheimer's 17,18 and Parkinson's disease 19 and amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 99%